2021
DOI: 10.15832/ankutbd.856762
|View full text |Cite
|
Sign up to set email alerts
|

Possibilities of Use Fertilizer Industry Waste Gypsum Material of Improve Sodic and Boron Soils

Abstract: The effect of the Fertilizer Industry Waste Gypsum Material (FIWGM) on the rehabilitation of barren soils has been investigated with this research. The soil improvement tests were carried out in randomized blocks with three replications and 0, 20, 40 and 60 tons ha -1 of FIWGM have been applied. By the intermittent ponding method, a total of 360 cm of water has been given, including 30 cm at each time. At the end of the trial, the application of FIWGM has showed positive effect on the physical and chemical pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
2

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 18 publications
(14 reference statements)
0
0
2
Order By: Relevance
“…The application of FGDG and biochar to saline-alkali soil (sandy soil) delayed infiltration, increased infiltration time, and decreased cumulative infiltration and infiltration capacity. These results contradict the findings of previous studies (Goncalo et al, 2020 ; Zhang et al, 2020a , b ; Bahceci et al, 2022 ). Zhang et al, ( 2020a , b ) demonstrated that the saturated water content and field water capacity of the biochar treatment significantly increased by 4.4% and 5.6%, respectively, after a short incubation period, and the combined application of gypsum and biochar significantly increased the soil-saturated hydraulic conductivity by 58.4% compared to the single application of either material.…”
Section: Resultscontrasting
confidence: 94%
See 1 more Smart Citation
“…The application of FGDG and biochar to saline-alkali soil (sandy soil) delayed infiltration, increased infiltration time, and decreased cumulative infiltration and infiltration capacity. These results contradict the findings of previous studies (Goncalo et al, 2020 ; Zhang et al, 2020a , b ; Bahceci et al, 2022 ). Zhang et al, ( 2020a , b ) demonstrated that the saturated water content and field water capacity of the biochar treatment significantly increased by 4.4% and 5.6%, respectively, after a short incubation period, and the combined application of gypsum and biochar significantly increased the soil-saturated hydraulic conductivity by 58.4% compared to the single application of either material.…”
Section: Resultscontrasting
confidence: 94%
“…In contrast, the texture of the saline-alkali soil was silt loam in Zhang et al ( 2020a , b ). Thus, the major difference between the findings of this study and those of Goncalo et al ( 2020 ), Zhang et al ( 2020a , b ), and Bahceci et al ( 2022 ) can be attributed to the variations in the soil type and texture, as well as the amounts and ratio of amendments. The effect of amendments on the soil structures with different textures varied significantly, with the types and amounts of amendments having a significant influence on the experimental results (Koralegedara et al, 2019 ; Saifullah et al, 2018 ; Singh et al, 2022 ).…”
Section: Resultscontrasting
confidence: 85%